Static bending and moisture response of cement-bonded particleboard produced at different levels of percent chemical additive content in board (2012)
A study was carried out to determine the optima level of percent additive concentration for wood cement board production from mixed tropical hardwoods species. Eight hardwood species used for the study are: Triplochiton scleroxylon K. Schum (Obeche). Terminalia ivorensis A. Chev. (Idigbo) Terminalia superb Eng. & Diets (Afara) Bruchystegia nigerica Hoyle & A.P.D. Jones (Okwen) Khaya ivorensis A. Chev. (Lagos Mahogany) Nesogordonia papaverifeni A. Chev. (Dantu-Oro) Tectona grandis Linn. F. (Teak) Gmelina arborea Roxb. (Gmelina). The experimental boards were made at five chemical additive content levels of 1.00%: 1.50%: 2.00%: 2.50% and 3.00% based on dry weight of cement in board, and three cement/wood mixing ratio levels of 2.25: 1.0. 2.50: 1.0 and 2.75:1.0. The experimental design is a two-factor factorial experiment, a combination of which manifested in 15 treatment combinations. The mean moduli of Rupture and Elasticity (MOR and MOE) obtained for each of the 15 treatment combinations in this experiment ranged from 3.28 to 10.46 N/mm2 while MOE values ranged from 2200 to 4010 N/mm2. The mean percent water absorption (WA) values ranged from 24.66 to 46.37% while the thickness swelling (TS) ranged from 0.98 to 3.62%. Statistical analysis showed chemical additive concentration and wood/cement ratio were found significant at 1% level of probability on the flexural and moisture properties. Stronger, stiffer and more dimensionally stable boards were produced at increasing levels of these two production variables. Also percent chemical additive content in board of 3.0% (Based on dry cement weight in board) performed best.